Expression and biochemical characterization of maltogenic amylase from bacillus lehensis G1 - Pachelles, Samson (2013)
This study was carried out for the expression and characterization of maltogenic amylase (MAG1) from Bacillus lehensis G1. Amplification of 1741 base pair gene fragments encoding MAG1 and expression in Escherichia coli have been successful. The expression of MAG1 was optimized at 30°C and 0.5 mM isopropyl ß-D-1-thiogalactopyranoside (IPTG) for a period of 12 hour post-induction time. Purification of the crude enzyme was done using the ACTAprime System which uses the concept of affinity chromatography. The optimum temperature and pH of the purified MAG1 were 40 °C and pH 7.0 respectively. The enzyme did not show potent thermostability and was stable at pH ranging from 7.0 to 9.0. The purified MAG1 has a preference towards cyclodextrin (CD) specifically ß-CD. Starches were least favored by MAG1 followed by pullulan. Only the metal ion Mn2+ increased the activity of MAG1 while K2+, Li2+ and Mg2+ slightly affect its activity. The metal ion Ca2+ significantly reduced MAG1 activity while Fe2+, Co2+, Zn2+, Cu2+, Pb2+ and Ni2+ drastically reduced the activity of MAG1. In terms of additives, only 2- mercaptoethanol (2-ME) managed to enhance the activity of MAG1 while ethylenediaminetetraacetic acid (EDTA) and Tween20 did not affect its activity. Drastic reduction of MAG1 activity was caused by phenylmethylsulfonyl fluoride (PMSF), sodium dodecyl sulfate (SDS), methanol and ethanol. The hydrolysis pattern of MAG1 was studied using CDs and maltooligosaccharides. The hydrolysis of CDs resulted in the formation of maltose but no glucose was detected. MAG1 was also able to linearize the CDs. MAG1 did not react with glucose, maltose and maltotriose but did react with maltotetraose, maltopentaose, maltohexaose and maltoheptaose to produce mainly maltose and maltotriose. The Km and Vmax of MAG1 towards ß-CD were 6.358 mg/mL and 91.63 µmol/min respectively